Diseño y realización de pruebas de simulación para determinar los parámetros críticos de coexistencia de los futuros servicios de Televisión Digital Terrestre DVB-T2 y las comunicaciones móviles LTE en Colombia. (2017)
The electric radio spectrum is a limited resource and with a high demand for use, so In particular, frequencies below 1 GHz meet physical characteristics that favor the transmission of digital terrestrial broadcasting signals and are especially attractive for mobile telecommunications systems, which has led to the competition of these services in very close bands. In this sense, the management of spectrum, is a fundamental task for the use and control of this resource. In the conference World Radio Conference of 2015 (WRC 15) the UHF sub-band was identified from 614 to 698MHz for the future use of IMT-2000 systems, including the LTE standard, inviting in this way to all the academic, governmental instances, and regulation, to develop studies on the operation of the different services in this band. This degree work took as an initial reference the studies developed in the different regions of the ITU on the interference phenomenon and the conditions of coexistence so that the LTE and DVB-T / T2 standards can coexist in the frequencies less than 1 GHz, the most relevant studies developed in this sense were consulted and were determined from these: the methods, tools and study variables used, as well as the cases and the study assumptions for each one of them. Of equal In this way, the current technical regulations and spectrum management plans were studied in Latin America and mainly in Colombia.